2013
DOI: 10.1016/j.ijgo.2013.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Association between tumor diameter and lymphovascular space invasion among women with early-stage endometrial cancer

Abstract: Tumor size greater than 2cm was significantly and independently associated with LVSI and myometrial invasion among patients with early-stage EC. Given the difficulty of obtaining reliable LVSI data from frozen sections, tumor size might be used as a surrogate at the time of surgery to provide additional information to triage patients for full surgical staging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…9 Our finding that patients with LVSI had higher preoperative and postoperative pathologic grade than did patients without LVSI is consistent with previous series. 4 found that in patients with lymph nodeYnegative disease, the presence of LVSI may be a more powerful prognostic marker than grade and histologic type.…”
Section: Discussionsupporting
confidence: 92%
“…9 Our finding that patients with LVSI had higher preoperative and postoperative pathologic grade than did patients without LVSI is consistent with previous series. 4 found that in patients with lymph nodeYnegative disease, the presence of LVSI may be a more powerful prognostic marker than grade and histologic type.…”
Section: Discussionsupporting
confidence: 92%
“…In an analysis of more than 300 endometrioid EC patients with FIGO grade 1 or 2 and myometrial invasion limited to the inner half, we found that no patients with tumor diameter of 2 cm or less had positive lymph nodes or lymph node recurrences or died of disease . This finding has been recently prospectively validated by our group and others …”
Section: Clinical Considerationssupporting
confidence: 71%
“…Considering the correlation between patient age and LVSI status, it is seen that there are publications which found both significant [3,33] and insignificant [27] correlations. Significant correlations have been reported between tumour size, [34,19] histological grade [19,33], and myometrial invasion [19,20,33]. These, along with the LUSI and LVSI statuses of patients, affect the decision to proceed with intraoperative lymphadenectomy in endometrial cancer surgery.…”
Section: Discussionmentioning
confidence: 99%